Effect of feeding urea-treated groundnut hulls (silage) and molasses during summer season on carcass characteristics of Desert lambs (Hammari subtype) under range condition - Ballal Ahmed, Abdelbagi; Ahmed Nour, Ikhlas; Musa Tibin, Ibrahim; Mustafa, Omer (Journal of Veterinary Medicine and Animal Production, 2022)
U. of K. J. Vet. Med. Anim. Prod., Vol. 5, Issue 2 (2014) p 66-73 ISSN: 243456 66 Effect of feeding urea-treated groundnut hulls (silage) and molasses during summer season on carcass characteristics of Desert lambs (Hammari subtype) under range condition Abdelbagi Ballal Ahmed1, Ikhlas Ahmed Nour2; Ibrahim Musa Tibin3; Omer Mustafa4 1 Abstract: The study was conducted at Elnuhood Desert Sheep Research Station, North Kurdofan State, Sudan, during late summer season; to evaluate the effect of supplementation of urea-treated groundnut hulls silage and molasses on slaughter weight and carcass characteristic of desert lamb Hammari ecotype. The duration of the experiment was 90 days, 60 lambs (thirty males + thirty females) of 6 months average age and 23.4 kg average live weight were divided into three equal groups(A,B, and C) of twenty lambs(10 males + 10 females) each. Groundnut hulls treated with 5 % urea (of its weight) was ensiled for 30 days. Animal in group (A) and (B) were offered a diet composed of 77% treated groundnut hulls and 23 % molasses, while Group C was un -supplemented (the control) . All the groups were left to graze in the same way practiced by the nomads in the area. Slaughter weights, carcass weights, composition yield and non carcass components were determined. Supplementation had higher values for slaughter weight, hot and cold carcass weight, empty body weight, gut fill weight, subcutaneous fat thickness, eye muscle area and dressing percentage but the differences were not significant (p>0.05) compared to the free grazing un supplemented group( C control). Subcutaneous fat thickness, dressing percentage, leg and loin cuts, total muscle , total fat and trims were not significantly different among the groups but the meat: bone ratio was significantly higher in group A (2.4). Group A had the heaviest cuts than group B and C. Non carcass components were not significantly (p>0.05) different among the groups except for empty rumen and reproductive organs. Wholesale cuts weights increased but not significant (P>0.05) with increasing the dietary supplementation. Body fat depots of the supplemented lambs especially group A was increased compared with the un- supplemented group which had thinner subcutaneous fat cover. Key words: urea, groundnut hulls, silage, grazing, lamb carcass